The Philosophy of Critical Thinking in Problem-Based Science Learning - Ni Nyoman Sri Putu Verawati; Muhammad Sarjan (IKIP Mataram, 2023)
Exploration of effective pedagogical methods is the main focus aimed at cultivating not only specific knowledge of the subject matter but also critical thinking skills. Referring to the dynamics of exploring critical thinking skills, the role of critical thinking is considered highly important as a support for individual success, even regarded as a crucial skill. The current study aims to examine the role of critical thinking philosophy in Problem-Based Learning (PBL) in science education. This study is a literature review, where information and relevant data were sourced from Scopus and Google Scholar databases. The review findings reveal that science education is not just about knowledge of subject matter content but also about thinking skills. Critical thinking is deemed essential in the 21st century and requires stimuli to develop. One of the learning models that support the development of critical thinking is PBL. The literature review results also disclose the context of critical thinking philosophy, the concept of critical thinking, and critical thinking philosophy in PBL. Critical thinking is reflected in four key indicators: the ability to analyze, evaluate, inference, and decision-making. The review highlights how PBL facilitates critical thinking through engagement with complex problems, active learning, student autonomy, reflection, and repeated problem-solving. Thus, PBL aligns with philosophical principles emphasizing active engagement and experiential learning, inherently fostering students' critical thinking skills.